Lactic Acid Bacteria in Foodborne Hazards Reduction Physiology to Practice - Chen, Wei (Springer Singapore, 2018)
This book provides an overview of the physiological basis of lactic acid bacteria and their applications in minimizing foodborne risks, such as pathogens, heavy metal pollution, biotoxin contamination and food‐based allergies. While highlighting the mechanisms responsible for these biological effects, it also addresses the challenges and opportunities that lactic acid bacteria represent in food safety management. It offers a valuable resource for researchers, graduate students, nutritionists and product developers in the fields of food science and microbiology. .